2021
DOI: 10.1108/jhom-05-2020-0192
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the delivery of cancer pathways: a summary of the literature

Abstract: PurposeThe study aims to summarise the literature on cancer care pathways at the diagnostic and treatment phases. The objectives are to find factors influencing the delivery of cancer care pathways; to highlight any interrelating factors; to find gaps in the literature concerning areas of research; to summarise the strategies and recommendations implemented in the studies.Design/methodology/approachThe study used a qualitative approach and developed a causal loop diagram to summarise the current literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Insufficient samples in a lung cancer diagnosis not only affect patients' well‐being and outcomes but also strain the resources, the efficiency, and the reputation of healthcare institutions. Delays in treatment and missed opportunities for clinical trials increase workload and reduce efficiency 39–42 . Therefore, it is crucial for the healthcare providers to continuously work on improving the diagnostic techniques to minimize the occurrence of insufficient samples and ensure timely and accurate diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient samples in a lung cancer diagnosis not only affect patients' well‐being and outcomes but also strain the resources, the efficiency, and the reputation of healthcare institutions. Delays in treatment and missed opportunities for clinical trials increase workload and reduce efficiency 39–42 . Therefore, it is crucial for the healthcare providers to continuously work on improving the diagnostic techniques to minimize the occurrence of insufficient samples and ensure timely and accurate diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in treatment and missed opportunities for clinical trials increase workload and reduce efficiency. [39][40][41][42] Therefore, it is crucial for the healthcare providers to continuously work on improving the diagnostic techniques to minimize the occurrence of insufficient samples and ensure timely and accurate diagnoses.…”
Section: Laboratory Processingmentioning
confidence: 99%
“…Some studies used system dynamics modeling as part of a mixed methods study in conjunction with other methods, such as mixed integer programming [33] or qualitative interviews and surveys [34]. People were the primary unit being modeled in 50% of the studies (n = 16) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], while 16% modeled patient experience or behavior (n = 5) [50][51][52][53][54]. Other primary units modeled include cells (n = 4; 13%) [33, [55][56][57], environmental contaminants (n = 4; 13%) [58][59][60][61], currency (n = 2; 6%) [62,63], and web search queries (n = 1; 3%) [64].…”
Section: Plos Onementioning
confidence: 99%
“…Most studies of both types indicated more than one purpose. [34,35,49,[52][53][54], publicly available data from cancer registries or federal statistics (n = 7; 22%) [40,41,43,44,46,47,61], patient or health system data (n = 5; 16%) [34,37,45,51,53], literature review (n = 4; 13%) [36,48,50,62], and expert interviews (n = 4; 13%) [41,42,50,51]. One study used search engine data [64] and another used unpublished data from a previously conducted clinical trial [46].…”
Section: Plos Onementioning
confidence: 99%
“…However, gaps and biases within each system have been identified that undoubtedly affect the management of potentially curable patients. 17 There is a current lack of internationally agreed recommendations for improving care of lung cancer patients, with the purpose of being interpreted at a policy level to align efforts to empower those in positions to instigate change.…”
Section: Introductionmentioning
confidence: 99%